Nursing consultation in the family health strategy: challenges in the nursing process - Lima, Stella Godoy Silva e; Juliani, Carmen Maria Casquel Monti; Spagnuolo, Regina Stella; Carvalheira, Ana Paula Pinho; Penacci, Fernanda Augusta; Lima, Silvana Andréia Molina (JRG Journal of Academic Studies, 2024)
Objective: to understand the practice of the nursing process during consultations carried out by nurses in the Family Health Strategy. Method: qualitative study anchored in Grounded Theory, with 14 nurses working in the Family Health Strategy. Interviews were conducted using an open, non-directive technique, between 2017 and 2018, approved by the ethics committee. Three codings were used for analysis: open, axial and selective, which originated sub-process, theme and categories organized by the Strauss and Corbin paradigm. Results: the comparison of the data allowed the identification of the sub-process called “Nursing consultation in the practice of the Family Health Strategy” and the theme “Challenges in the Nursing Process” and its categories. Conclusion: The practice of Nursing Consultation has been developing over time with great challenges in the attempt to make it recognized. Investments in continuing education and training with subsidies for carrying out the consultation are necessary.